2020
DOI: 10.47197/retos.v0i39.82254
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do treinamento pliométrico sobre a impulsão vertical em atletas de futebol de campo na faixa etária de 15 a 18 anos: uma revisão sistemática (Effects of plyometric training on vertical jump in soccer players between 15 and 18 years old: a systema)

Abstract: Resumo. Introdução: O treinamento pliométrico (TP) é normalmente utilizado visando a melhoria da impulsão vertical (IV) e o desempenho físico de jogadores de futebol nas categorias de base. Objetivo: Verificar os efeitos do TP sobre a IV em atletas de futebol de campo na faixa etária de 15 a 18 anos de idade. Métodos: Esta revisão sistemática seguiu as recomendações PRISMA. A pesquisa foi realizada nas bases científicas LILACS (via BVS), MEDLINE (via PubMed), Cochrane, SciELO, Scopus, ScienceDirect, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(77 reference statements)
0
1
0
1
Order By: Relevance
“…Traditionally, plyometrics training was damaging for young population, since it increased injury risk and growth delay (Lloyd et al, 2014). However, recent studies have shown that plyometric training could be beneficial effects for young soccer players when the appropriate training rules for their age are followed (Bedoya, Miltenberger, & López, 2015;Falces-Prieto et al, 2018;Fonseca et al, 2020). Actually, plyometrics training has been recommended to improve vertical and horizontal jump ability (Asadi, Ramírez-Campillo, Arazi, Sáez de Villarreal, 2018;Zisis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, plyometrics training was damaging for young population, since it increased injury risk and growth delay (Lloyd et al, 2014). However, recent studies have shown that plyometric training could be beneficial effects for young soccer players when the appropriate training rules for their age are followed (Bedoya, Miltenberger, & López, 2015;Falces-Prieto et al, 2018;Fonseca et al, 2020). Actually, plyometrics training has been recommended to improve vertical and horizontal jump ability (Asadi, Ramírez-Campillo, Arazi, Sáez de Villarreal, 2018;Zisis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…La pliometría es un entrenamiento de resistencia por lo que debe seguir los principios de sobrecarga progresiva, incrementando de forma sistemática la frecuencia, volumen e intensidad del entrenamiento en función de la temporada (Haff & Triplett, 2017, p. 1029. Este entrenamiento es un método muy popular de acondicionamiento físico en adultos (Markovic & Mikulic, 2010) y jóvenes (Fonseca, et al, 2020). Básicamente, consiste en realizar ejercicios de salto con el peso del cuerpo utilizando la acción muscular que mejora la capacidad de los sistemas neural y musculo-tendinoso para producir la máxima fuerza en el menor tiempo posible (Markovic & Mikulic, 2010).…”
Section: Entrenamiento De Pliometría Para La Optimización Del Saltounclassified
“…The different areas of knowledge among which medicine, biochemistry, and social sciences, among others, have allowed the study of sports over time and with this, sports science has sought to promote the understanding of the adaptive processes of athletes in response to training and competition (Bishop, 2008;Ford et al, 2011;Fullagar et al, 2019;Becerra Patiño et al, 2020;Becerra Patiño & Escorcia, 2023;Becerra-Patiño et al, 2023). Within the processes that have been advancing in short, medium, and longterm sports preparation (Balyi & Way, 1995;Balyi & Hamilton, 2004) the development of physical capacities has been a common denominator in the different research proposals (García-Pinillos, Ruiz-Ariza & Latorre-Román, 2015;Falces-Prieto et al, 2021;Fonseca et al, 2021;Becerra Patiño, Sarria Lozano & Prada Clavijo, 2022;Becerra Patiño, Sarria Lozano & Palomino, 2023).…”
Section: Introductionmentioning
confidence: 99%